A interferência da modalidade oral no texto escrito um enfoque da linguística sistêmico-funcional - Silva, Samuel da (2017)
The difficulty that writing production represents for most students is present in the discourse of teachers and researchers from the most diverse areas, especially with reference to the writing of the argumentative-essay text, since this is the type of text which is most requested both in high school/university environments and in university entrance exams in Brazil. There are several questions waiting for answers. Why does the linguistic proficiency of the students, who can communicate orally without any problems in their daily lives, decline when they express themselves in the written modality? As writing occurs after the acquisition of the oral modality, the hypothesis that arises naturally is that this decline would result from the transposition of the oral features to the writing ones without the due adjustments that this requires because of the contextual and functional differences that distinguish one of the other. But, after all, what elements exist in face-to-face interaction that differ from those required, for example, by a formal academic text? The purpose of this research is to examine the characteristics of a text of the oral modality - a dialogue between a psychologist and an engineer - as well as texts of the written modality - a model argumentative essay requested from third year high school students in order to verify the interference of the oral modality in the students’ writing. Among the several factors that distinguish the two modalities, this research focuses on the structural unit, involving structures of genre with their stages and purposes and texture structure, covering the lexicogrammatical choices with implications for coherence and cohesion. The research responds to the following questions: (a) in the comparison of the oral modality with the formal written modality, what differences are there regarding genre structure and texture structure? (b) What can this comparison provide for the understanding of the failures committed in a argumentative-essay text of candidates for university entrance exams? The results of the research show that the difficulty of the students in writing the written text may arise from the differences between the modalities, be it in structuring, or in the lexicogrammatical choices. The oral modality syntax presents itself with characteristics specific to it, which must be replace or complemented by wrinting